2011
DOI: 10.1200/jco.2010.30.4386
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Trial of Weekly Methotrexate or Pulsed Dactinomycin for Low-Risk Gestational Trophoblastic Neoplasia: A Gynecologic Oncology Group Study

Abstract: A B S T R A C T PurposeThere is no consensus on the best regimen for the primary treatment of low-risk gestational trophoblastic neoplasia (GTN). Patients and MethodsTwo commonly used single-drug regimens were compared with respect to the proportion of patients meeting the criteria for a complete response (CR) in a randomized phase III trial conducted by the Gynecologic Oncology Group. Eligibility was purposefully broad to maximize the generalizability of the results and included patients with a WHO risk score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
124
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(131 citation statements)
references
References 18 publications
3
124
4
Order By: Relevance
“…There is increasing interest in using pulsed or 5-day actinomycin D rather than MTX-FA as the initial therapy for low-risk treatment, as this single-agent alternative may produce a slightly improved chance of inducing remission (Gilani et al, 2005;Osborne et al, 2008;Yarandi et al, 2008). It is also thought that actinomycin D may result in a shorter duration of treatment.…”
mentioning
confidence: 99%
“…There is increasing interest in using pulsed or 5-day actinomycin D rather than MTX-FA as the initial therapy for low-risk treatment, as this single-agent alternative may produce a slightly improved chance of inducing remission (Gilani et al, 2005;Osborne et al, 2008;Yarandi et al, 2008). It is also thought that actinomycin D may result in a shorter duration of treatment.…”
mentioning
confidence: 99%
“…A variety of regimens have been developed, in which non-randomized, mostly retrospective studies demonstrate a 50-90% chance of inducing remission 22 . Osborne et al 16 have suggested that pulsed Act-D is more likely to induce remission than weekly MTX but this randomized study has been underpowered. We are waiting for the results of an larger international trial run by the Gynecology Oncology Group in the United States, begun in 2013 (NCT01535053), evaluating quality of life and acceptability of treatment with the objective of helping to define the optimum single-agent approach 17,23 .…”
Section: Discussionmentioning
confidence: 97%
“…Usually, it is administered using a 5-day EV schedule in the cases of MTX resistance or toxicity 8,11,12 . In order to reduce the high rate and intensity of collateral effects with 5-day Act-D schedule, several authors have investigated the use of the so-called pulsed Act-D regimen 15,16 . When used as first-line ChT for low-risk GTN patients, pulsed Act-D had the following results in 4 studies: mean number of courses was 4.9 -our results, median 2; resistance was 8-24% -our results, 32.9%; and cure rate ranged from 76% (low-risk metastatic GTN) to 86% (non-metastatic GTN) -our results, 67.1%, with most patients in stage I of FIGO 2002 12,13,16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In The Cochrane review, Alazzam et al aimed to determine the efficacy and safety of first line chemotherapy in the treatment of low risk GTN [5]. The review included randomised controlled trials (RCTs) [6] [7], quasi-RCTs [8]- [10] and non-RCTs (cohort and case control studies (CCS) [11] [12]) for the treatment of low risk GTN. Eight studies met the review entry criteria (n = 769).…”
Section: Discussionmentioning
confidence: 99%